Isolation: The experience of adolescent motherhood in Laos - Thongmixay, Souksamone; Essink, Dirk; Kahrs, Taewee; Vongxay, Viengnakhone; Wright, Pamela; Sychareun, Vanphanom; Broerse, Jacqueline E. W. (Frontiers in Global Women's Health, 2023)
Background: Teenage pregnancy is a persistent public health problem with pervasive socio-economic consequences, particularly in in low- and middle-income countries, often related to low social participation and low economic security. The experiences of adolescent pregnancy and motherhood have seldom been described from a personal point of view. This study aimed to gain insights into how peri-urban adolescent mothers in Lao PDR experience their motherhood, to describe how they perceive their situation and try to cope with it. Methods: This qualitative study undertaken with pregnant adolescents and young mothers living in peri-urban areas in two of the 18 provinces in Lao PDR, data were collected from 20 respondents, using semi-structured interviews (n=20), followed by two focus group discussions (n=10). In all but two cases, the pregnancy was unintended. Results: Mothers’ experience navigating exclusion was the most significant theme and was experienced individually, socially and in relation to official systems. All mothers were determined to be good mothers, but were overwhelmed and unsure how to overcome structural barriers to educational, social and economic participation. Conclusion: Participants reflected on adolescent pregnancy as tied to losses of past and future aspirations, and believed that working to prevent unintended adolescent pregnancy is worthwhile, but also advised that structures for community support would help young women in their position.